Role of pipelle versus dilatation and curettage in tissue diagnosis abnormal uterine bleeding - Balaram, Markad Swapnil; Shinde, Roopa R.; Babu, C. Suresh; Mubasher, Hamid Mubashar Mohamed; Shinde, Ranoji Vijaysing (International Journal of Research in Medical Sciences, 2020)
Background: Menstrual irregularities and abnormal heavy menstruation account for up to 26-35% of women attending Gynecological outpatient Department. Abnormal Uterine Bleeding (AUB), it is more common at extremes of age endometrial hyperplasia occurs in 5-10% of patients with post-menopausal bleeding out of which atypical hyperplasia has 26-32 % risk of having malignancy in future. Therefore, endometrial sampling for histopathology is important in the assessment of abnormal uterine bleeding is mandatory. Our study was conductive to know the effectiveness of pipelle type devices, versus Dilatation and curettage in obtaining quality endometrial tissue for histopathological examination. Methods: The study was undertaken in Department of obstetrics and gynaecology along with department of Pathology at Rajarshi Chhatrapati Shahu Maharaj, government medical college, Kolhapur after getting approval from the Hospital Committee on Clinical Research and Ethical Committee of the institution, during the period from October 2016 to March 2017 (six months). Total number of subjects included in study is Hundred after taking into consideration of inclusion and exclusion criteria. Results: The ease of doing procedure was much easier as compared to D&C and the Tissue sample obtained for histopathological examination were as par D&C. It was concluded that histopathology report was available in 92 of the 100 pipelle samples and 93 of 100 D&C samples. It was also, observed that increased endometrial thickness was not always associated with adequate tissue diagnosis. Conclusions: Pipelle is simple, affordable, patient friendly can be easily performed with minimal training, which can be performed in Outpatient Gynaecological Department. The diagnostic value and positive predictive value of Pipelle is at par with conventional D&C. So, pipelle can be recommended for all perimenopausal patients with AUB to rule out various, premalignant and malignant conditions of the endometrium.